Hepatoma targeting peptide conjugated bio-reducible polymer complexed with oncolytic adenovirus for cancer gene therapy - Choi, Joung-Woo (J Control Release, 2015)
Despite adenovirus (Ad) vector’s numerous advantages for cancer gene therapy, such as high ability of endosomal escape, efficient nuclear entry mechanism, and high transduction, and therapeutic efficacy, tumor specific targeting and antiviral immune response still remain as a critical challenge in clinical setting. To overcome these obstacles and achieve cancer-specific targeting, we constructed tumor targeting bioreducible polymer, an arginine grafted bio-reducible polymer (ABP)-PEG-HCBP1, by conjugating PEGylated ABP with HCBP1 peptides which has high affinity and selectivity towards hepatoma. The ABP-PEG-HCBP1-conjugated replication incompetent GFP-expressing ad, (Ad/GFP)-ABP-PEG-HCBP1, showed a hepatoma cancer specific uptake and transduction compared to either naked Ad/GFP or Ad/GFP-ABP. Competition assays demonstrated that Ad/GFP-ABP-PEG-HCBP1-mediated transduction was specifically inhibited by HCBP1 peptide rather than coxsackie and adenovirus receptor specific antibody. In addition, ABP-PEG-HCBP1 can protect biological activity of Ad against serum, and considerably reduced both innate and adaptive immune response against Ad. shMet-expressing oncolytic Ad (oAd; RdB/shMet) complexed with ABP-PEG-HCBP1 delivered oAd efficiently into hepatoma cancer cells. The oAd/ABP-PEG-HCBP1 demonstrated enhanced cancer cell killing efficacy in comparison to oAd/ABP complex. Furthermore, Huh7 and HT1080 cancer cells treated with oAd/shMet-ABP-PEG-HCBP1 complex had significantly decreased Met and VEGF expression in hepatoma cancer, but not in non-hepatoma cancer. In sum, these results suggest that HCBP1-conjugated bioreducible polymer could be used to deliver oncolytic Ad safely and efficiently to treat hepatoma.